Effectiveness of Animated Educational Videos in Reducing Anxiety Among Hospitalized Preschool Children - Hendra, Agus; Yusuf, Muhamad Rafhi (Medical-Surgical Journal of Nursing Research, 2025)
Background: Hospitalization can be a distressing experience for children and frequently triggers anxiety, particularly among preschool-aged children who have limited cognitive and emotional coping abilities. Anxiety during hospitalization may disrupt the healing process, reduce cooperation with medical procedures, and potentially lead to long-term psychological trauma. Therefore, effective non-pharmacological interventions are essential to minimize anxiety in this age group. Animated educational videos have been proposed as a distraction-based intervention to help children cope with stressful hospital environments. Objective: This study aimed to examine the effectiveness of animated educational videos in reducing anxiety levels among hospitalized preschool children. Methods: A quantitative study with a quasi-experimental design was conducted involving 60 preschool children aged 3–6 years who had been hospitalized for more than two days. Participants were selected using convenience sampling. Children with mild anxiety whose parents provided informed consent were included, while those in critical condition or receiving intensive care were excluded. Anxiety levels were assessed using the Spence Children’s Anxiety Scale (SCAS). Data analysis was performed using the Wilcoxon Signed Ranks Test and the Mann–Whitney test. Results: The findings revealed a statistically significant reduction in anxiety levels among preschool children following exposure to animated educational videos (p = 0.000). Conclusion: Animated educational videos are effective in reducing anxiety among hospitalized preschool children and may be implemented as a simple, safe, and non-pharmacological intervention in pediatric nursing practice.